Studying X-ray spectra from large-scale jets of FR II radio galaxies: application of shear particle acceleration - He, Jia-Chun; Sun, Xiao-Na; Wang, Jie-Shuang; Rieger, Frank M.; Liu, Ruo-Yu; Liang, En-Wei (Monthly notices of the Royal Astronomical Society, 2023)
Shear particle acceleration is a promising candidate for the origin of extended high-energy emission in extra-galactic jets. In this paper, we explore the applicability of a shear model to 24 X-ray knots in the large-scale jets of FR II radio galaxies and study the jet properties by modelling the multiwavelength spectral energy distributions (SEDs) in a leptonic framework including synchrotron and inverse Compton-CMB processes. In order to improve spectral modelling, we analyse Fermi-LAT data for five sources and reanalyse archival data of Chandra on 15 knots, exploring the radio to X-ray connection. We show that the X-ray SEDs of these knots can be satisfactorily modelled by synchrotron radiation from a second, shear-accelerated electron population reaching multi-TeV energies. The inferred flow speeds are compatible with large-scale jets being mildly relativistic. We explore two different shear flow profiles (i.e. linearly decreasing and power law) and find that the required spine speeds differ only slightly, supporting the notion that for higher flow speeds the variations in particle spectral indices are less dependent on the presumed velocity profile. The derived magnetic field strengths are in the range of a few to 10 µG and the required power in non-thermal particles is typically well below the Eddington constraint. Finally, the inferred parameters are used to constrain the potential of FR II jets as possible ultra-high-energy cosmic-ray accelerators.
Veröffentlicht: 31. August 2023
Gesehen am 25.07.2024